Penetapan Balance Scorecard untuk Mengukur Kinerja Sistem dan Teknologi Informasi di PT. DXY, Jakarta - Hudiarto Hudiarto; Fury Arifin (ULTIMA InfoSys, 2014)
Changing of country’s leadership will affect state policy in Indonesia. It will automatically change its policies and business processess gradually to make it more clean, well controlled, and more transparant. In this case, it might affect some companies that previously their business rely on the power of negotiation business practice and relationships for achieving a project. That companies will start losing their customers especially from the government and state-owned bank (SOEs) in the future. PT. DXY is a medium scale company engaged in mining industry, particularly in supplying various type of heavy equipments and other support services. The shareholders and the board of directors aware of this situation and they are ready to find a way to transform. Through various stages of approach, especially in usage of the IS / IT from Primozic, SWOT Analysis, Balanced Scorecard, and New Information Economics, they drafted business plans, and information systems and technology (IS/IT) strategies so that the company can still exist and even be able to occupy higher position in the competition of the industry. One that can be addressed here is the new Balanced Scorecard that is used as the benchmark performance management at the company for the first time. Changes in business processes as well as investments in the near future on the IS/IT cover human resource (HR) and customer resource management (CRM) applications along with forming computer networking. It is believed to be able to change the position of the use of IS/IT from what is now saving money becoming making money. Index Terms: balance scorecard, information system and technology, make money, save money, state policy.